The Development of Scientific Literacy-Based Biology Textbook for High School Students - Natalina, Mariani; Shafii, Wan; Prasono, Awanda (Proceedings of the UR International Conference on Educational Sciences, 2018)
Scientific Literacy-Based Biology Textbook can be used to improve the literacy of science of senior high school students. This research aims to provide a qualified scientific literacy-based biology textbook. The research consists of the stages of analysis, design, and development. This book was developed based on the analysis of question items of the PISA 2006 and 2015 as well as linkages with the basic competency of curriculum 2013. The stage of analysis, design, development, internal validation and test I carried out in the biology laboratory of FKIP Universitas Riau. The external validation and testing II implemented in SMA Negeri 1 Pekanbaru. The analysis of question items of the PISA 2006 and 2015 produce four topics which are developed; Methods, biodiversity, evolution, and biotechnology. This book was validated based on three aspects of scientific literacy: aspects of the format of the book and the graphic, aspect of content eligibility and scientific literacy. The contents eligibility includes the technique of presentation and scientific literacy includes science as the torso, science as a way of investigating, science as a way of thinking, and scientific as interaction between the science technology and society. The third aspect is the aspect of language. Scientific literacy-based biology textbook that is produced in this research is at a very valid category and very good so it is appropriate to be used as a source of autodidact learning in developing scientific literacy ability.